2020
DOI: 10.3389/fvets.2020.00349
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal Development and Histomorphometry of Broiler Chickens Fed Trichoderma reesei Degraded Date Seed Diets

Abstract: A study was conducted to investigate the impact of degraded date pits (DDP) on the development and morphology of the intestine in broilers. Trichoderma reesei was used to produce the DDP using a solid-state degradation method. One hundred and eighty broilers were divided into six treatments in triplicate groups of 10 chicks each. The dietary treatments were: positive control with corn-soy basal diet, negative control with corn-soy basal diet + 20% oxytetracycline at 0.05%, corn-soy basal diet + 10% DDP, cornso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…FMT also improved the intestinal morphology in broiler by increasing the thickness of its serous membrane and muscle layers [20]. Due to the jejunum's unique features, i.e., efficient nutrients absorption via the largest surface area [23], and efficient nutrient translocation via active vascular system of villi [24], nutrient absorption/ intake mainly occurs in the jejunum. The jejunal histomorphology is a good indicator for digestive/absorptive ability [25].…”
Section: Introductionmentioning
confidence: 99%
“…FMT also improved the intestinal morphology in broiler by increasing the thickness of its serous membrane and muscle layers [20]. Due to the jejunum's unique features, i.e., efficient nutrients absorption via the largest surface area [23], and efficient nutrient translocation via active vascular system of villi [24], nutrient absorption/ intake mainly occurs in the jejunum. The jejunal histomorphology is a good indicator for digestive/absorptive ability [25].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, significant increases in the abundance of the microbiota and the lengths of the jejunum and ileum in this group were observed. Nutrient assimilation is enhanced with increasing intestinal length, which also results in a greater surface area of interaction between food and the intestine (Alyileili et al, 2020; Reece, 2017). Hence, it could be concluded that Eucommia ulmoides supplementation may promote the contact between food and I cells in the intestine by increasing the length of the intestine, which in turn promotes the secretion of cholecystokinin and regulates pancreatic secretion, thus facilitating the promotion of the digestion and absorption of nutrients.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, there have been trends to utilize the phytochemical properties of industrial fruit or herbs wastes in animal feeding, which will not only reduce environmental burdens, but also improve animal production and health [ 47 , 48 ]. Similarly, phytochemical or nutraceutical prosperities of date pit or waste have been explored or attempts have been made to improve them using solid state degradation by Trichoderma reesei L. and their utilization in animal feeds [ 49 , 50 , 51 , 52 , 53 ]. Alyileili et al [ 49 ] reported that solid state degradation of date pit with T. reesei enhanced mannan oligosaccharide content, phenolic (142 g gallic equivalent/kg) and flavonoid (117 g rutin equivalent/kg) content of degraded date pits and antioxidant activities.…”
Section: Recent Knowledge and Future Directionmentioning
confidence: 99%
“…The inclusion of 10% degraded date pits (phenolics, flavonoids and mannan–oligosaccharide) in the diets of broiler chickens increased catalase, superoxide dismutase and glutathione peroxidase activities in the serum, liver, and intestine, and decreased malondialdehyde content compared to the control group [ 50 ]. It also increased pancreatic enzyme activities, the villus length, and the villus/crypt ratio, and decreased the crypt depth of the intestine [ 51 ]. The number of pathogenic bacteria such as Escherichia coli, Enterobacteriacea, Salmonella , and Shigella were reduced, but beneficial bacteria such as Bifidobacterium and Lactobacillus were increased in the gut of poultry by 10% degraded date pits [ 52 ].…”
Section: Recent Knowledge and Future Directionmentioning
confidence: 99%